Differential response patterns to disgust-related pictures. Issue 8 (17th November 2018) - Fink, Jakob; Buchta, Frederike; Exner, Cornelia
ABSTRACT: In the present study, attentional bias was investigated as a potential predisposing mechanism for the contamination-related subtype of obsessive-compulsive disorder (C-OC disorder). Fifty healthy participants with varying degrees of subclinical C-OC symptoms performed a visual search task to measure differential attentional biases elicited by neutral, disgust-, and fear-specific pictorial material. Participants had to find a target picture within five neutral distractor pictures randomly presented on different locations in an array. The task was to decide whether the array contained an unpleasant target picture or not. In randomly-selected emotional trials, participants were further asked about the content of the picture and the confidence of their answer. The results show that the reaction times significantly differed between the emotional and neutral pictures. Participants were significantly more confident in answering questions referring to fear compared to disgust pictures. This effect was marginally amplified in participants with higher C-OC symptoms. We discuss the results within the framework of the cost and benefit hypothesis, which postulates that disgust evolutionarily elicits stronger uncertainty compared to fear, owing to the ambiguous nature of the stimuli. Increased uncertainty might be an important but underestimated factor for pathological disgust experience, such as in obsessive-compulsive disorder.